Analysis of Mathematics Creative Thinking Ability in Each Gregorc Mind Styles with a Project-Based E-Learning Model - Detalia Noriza Munahefi; Mulyono Mulyono; Kartono Kartono (SEAMEO Regional Centre for QITEP in Mathematics, 2025)
The difference in mind styles is one of the challenges to improving students' mathematical creative thinking ability—learning activities with a project-based e-learning model as an alternative to solve problems. The research aims to describe mathematical creative thinking ability in Gregorc mind styles with a project-based e-learning model. Gregorc mind style consists of concrete sequential (CS), abstract sequential (AS), concrete random (CR), and abstract random (AR). The mixed research method begins with quantitative research and then continues qualitatively. This research was conducted on vector material for class X high school students. The sampling technique is a probabilistic stratified sampling type where samples are taken in each Gregorc mind style with proportions according to their presence in the population. Students with CS mind styles dominated the results of the study. At the same time, students with AS mind styles were not found. The ANOVA test showed a significance value of 0,952 > 0,05, so there was no difference in mathematical creative thinking abilities in Gregorc's mind styles. However, every student with different mind styles has different achievement aspects of mathematical creative thinking ability. Therefore, three subjects were taken using each Gregorc mind style in the qualitative research stage. Students with the CS mind style can achieve the elaboration aspect well, but the originality aspect cannot be completed well. On the other hand, the originality aspect can be achieved very well by students with an AR mind style.